Cyclooxygenase-2 Expression Is a Predictive Marker for Late Recurrence in Colorectal Cancer - Sung Hoo Kim; Byung Kyu Ahn; Seung Sam Paik; Kang Hong Lee (Gastroenterology Research and Practice)
Introduction. Cyclooxygenase-2 (COX-2) expression is elevated in colorectal cancer (CRC). However, data about the relation between COX-2 expression and the impact on the biologic behavior of recurrent disease are inconclusive as yet. The aim of this study is to investigate the relationship between the status of COX-2 expression in the primary CRC and the characteristics of recurrence after curative resection of stage I to III CRC. Materials and Methods. Ninety-eight patients with recurrence in 376 CRC patients, who underwent curative surgery between January 1991 and August 2001, were retrospectively assessed. Immunohistochemical staining, performed for the presence of COX-2 on tissue microarrays, was analyzed. Results. Forty-six patients showed elevated COX-2 expression, and 52 patients did not. The mean time to recurrence was significantly longer in the positive group than in the negative group (34.1 months ± 30.0 versus 21.9 months ± 17.4; P=0.019). Positive COX-2 expression was correlated with late recurrence (>3 years after surgery) [43.5% versus 13.5%; P=0.001]. In multivariate analysis, COX-2 expression was an independent factor associated with late recurrence (OR 4.656; 95% CI, 1.696 to 12.779; P=0.003). Recurrence pattern and postrecurrence survival were not different between the two groups. Conclusions. Elevated COX-2 expression in itself is not a prognostic factor, but COX-2 expression in tumor tissue may be an independent predictive marker of late recurrence for patients with stage I to III CRC.